O ensino de ciências e a pesquisa em sala de aula na perspectiva de pais e alunos - Delord, Gabriela Carolina Cattani (2012)
With the increase of scientific publications in recent decades, especially based on innovative practices, the result would be expected that these changes bring to the Teaching of Science. However, it is clear that the transmissive teaching is still prevalent in most schools. In fact, academic research has not changed on a large scale, the traditional practice of teaching. Several studies try to identify what is the best way to learn or how we teach in the classroom, in most cases, aiming at a science education that reflects the reality of the students. From desk research, theses and dissertations was found that for the realization of innovative practices in the classroom are considered, in most cases, only evaluations of researchers and teachers on these, as parents and students were not actors of Science Education. This dissertation argues that we need to learn science from common sense and the problems that arise in daily from the ongoing dialogue with parents and students. Still, the dissertation is characterized by investing in a qualitative study in which the instrument of data collection is presented from the method of focus groups and questionnaires. The subjects were investigating twenty-two students of municipal schools in Guaíba, Rio Grande do Sul and sixty parents of students in their schools. The subjects were asked about what they perceive Education in Science and how they evaluated the methodological practice of Education by Research in the classroom. From the analysis it was concluded that parents and students can also be actors of scientific research evaluating innovative practices, suggesting models of teaching and learning as contextualizing the experiences brought from outside the school. Still, from the dialogue with the families we know more students adapting this knowledge in school practices.